Meeting dedicated to the centenary of the First International, Tuesday, September 29, 1964 - Chroesjtsjov, Nikita; Ponomariov, Boris (Moscow : Novosti, 1964)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Eerste Internationale (1864-1876).